Has the pandemic exacerbated alcohol harm?. Issue 4 (19th July 2022) - Gilmore, William; Gilmore, Sir Ian
Abstract : Men have always been at greater risk of harm than women from alcohol use, but the pandemic may have exacerbated the problem. Healthcare professionals can support public health colleagues in calling for government‐led initiatives to tackle alcohol availability.